CAP Theorem between Claims and Misunderstandings: What is to be Sacrificed? - Diack, Balla Wade; Ndiaye, Samba; Slimani, Yahya (International Journal of Advanced Science and Technology, 2013)
Modern large distributed Systems at wide scale have adopted new types of databases that are not subject to the features which ensure strong Consistency. In this paper, we discuss the CAP theorem, its evolution and its influence on these systems. After, we talk about the misunderstandings and problems aroused by this theorem. Finally, we give the updates on CAP brought by some researchers.